E3710, Long-Acting PPI as New Approach for the Treatment of Unmet Medical Needs for GERD - Kodama, Kotaro; Fujisaki, Hideaki; Tonomura, Hideo; Jindo, Miwa; Watanabe, Misako; Nagakawa, Junichi; Takeguchi, Noriaki (IntechOpen, 2012)
None